Analysis of the national school feeding program in the municipality of Viçosa, state of Minas Gerais - Naruna Pereira Rocha; Mariana De Santis Filgueiras; Fernanda Martins de Albuquerque; Luana Cupertino Milagres; Ana Paula Pereira Castro; Mariane Alves Silva; Glauce Dias da Costa; Silvia Eloiza Priore; Juliana Farias de Novaes (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze the implementation of the Brazilian National School Feeding Program as a food and nutritional security policy in public schools. METHODS This a cross-sectional study, with a quantitative and qualitative approach, carried out with 268 schoolchildren aged eight to nine years from the public school system of Viçosa, state of Minas Gerais, Brazil, in 2015. Interviews were carried out using semi-structured questionnaires with the children, parents, cooks, nutritionists, trainer of the Technical Assistance and Rural Extension Company, and president of the School Feeding Council. In order to analyze the implementation of the National School Feeding Program in Viçosa, we evaluated the direct weighing of the food served in the schools using mechanical balances with a capacity of up to 10 kg and the perception of the social players involved in the implementation of the National School Feeding Program. The children were questioned about the acceptance of and adherence to the food offered, in addition to the habit of bringing food from home. Parents reported knowledge about the School Feeding Program and Council. The qualitative analysis consisted of content analysis and quantitative analysis using the chi-square test, Fisher's exact test, and Mann-Whitney test. We adopted the statistical significance of 5% for quantitative analysis. RESULTS Children reported low adherence to the school feeding program and most of them used to bring food from home. Irregularities were identified in the implementation of the National School Feeding Program, such as: inadequate number of nutritionists, suspension of Council meetings, inadequate infrastructure in the areas of preparation and distribution of meals, lack of training of cooks, lack of nutritional adequacy of the food offered, and lack of actions on food and nutritional education. The Program complied with the recommendations for purchasing food from family farms. CONCLUSIONS The National School Feeding Program presented many irregularities in Viçosa. It is important to monitor the problems identified for better reformulation and planning of the Program, in order to guarantee the food and nutritional security of the children served.